Adaptive output feedback control for a class of non-affine nonlinear systems. Issue 4 (3rd April 2021) - Wang, Yubing; Bai, Peng; Liang, Xiaolong; Zhang, Jiaqiang
Abstract : The adaptive tracking control problem of a class of uncertain SISO non-affine nonlinear systems is considered under the condition that system states are immeasurable and non-affine nonlinear function is possibly discontinuous. In order to remove the restriction that non-affine nonlinear function must be continuous, a novel model is developed for the non-affine nonlinear function. Combined with this model, an adaptive output feedback controller is proposed by utilising a high gain observer to estimate the immeasurable system states. It is proved that all the signals in the closed-loop system are bounded and the tracking error can be made arbitrarily small by choosing appropriately design parameters. Finally, simulation example is provided to demonstrate the effectiveness of the proposed approach.